2022
DOI: 10.21203/rs.3.rs-1778084/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Folate ameliorates arrhythmia in patient-derived TANGO2-deficient iPSC-cardiomyocytes

Abstract: TANGO2-deficient disorder (TDD) is an autosomal recessive genetic disease caused by biallelic loss-of-function variants in TANGO2 gene. TDD-associated cardiac arrythmias are typically recalcitrant to standard antiarrhythmic medications and constitute the leading cause of death. Here, we established novel patient-derived induced pluripotent stem cell differentiated cardiomyocyte (iPSC-CM) models that recapitulate key electrophysiological abnormalities in TDD including prolonged field potential duration, prematu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
3
1
0
Order By: Relevance
“…A recent study suggests that folic acid (vitamin B9) can restore normal rhythm in a patient-derived cardiomyocyte model system. 22 Together with our present study this suggests that several B complex vitamins may have beneficial effects on various clinical aspects of this disease. Consistent with this notion, a natural history study of over 70 individuals suffering from TDD found that metabolic crises were not seen in individuals taking a multivitamin or a B complex supplement.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A recent study suggests that folic acid (vitamin B9) can restore normal rhythm in a patient-derived cardiomyocyte model system. 22 Together with our present study this suggests that several B complex vitamins may have beneficial effects on various clinical aspects of this disease. Consistent with this notion, a natural history study of over 70 individuals suffering from TDD found that metabolic crises were not seen in individuals taking a multivitamin or a B complex supplement.…”
Section: Discussionsupporting
confidence: 84%
“…To date, there are no treatment options for individuals suffering from TDD. A recent study suggests that folic acid (vitamin B9) can restore normal rhythm in a patient‐derived cardiomyocyte model system 22 . Together with our present study this suggests that several B complex vitamins may have beneficial effects on various clinical aspects of this disease.…”
Section: Discussionsupporting
confidence: 84%
“…A recent study suggests that folic acid (vitamin B9) can restore normal rhythm in a patient-derived cardiomyocyte model system. 22 Together with our present study this suggests that several B complex vitamins may have beneficial effects on various clinical aspects of this disease.…”
Section: Discussionsupporting
confidence: 84%
“…To optimize treatment plans for patients with TDD, several studies have further assessed the effect of individual B vitamins in patients and disease models. For example, in a recent preprint, vitamin B9 (folate) treatment of cardiomyocyte cell lines generated from patient-derived induced pluripotent stem cells ( Zhang et al, 2022 preprint) notably decreased premature ventricular contractions within 4-12 h of treatment. This did not have any significant effect on corrected QT interval (QTc) prolongation, which is a heart rate measurement used to detect arrythmia.…”
Section: Vitamin B Treatment Indicates That Lipid Homeostasis Defects...mentioning
confidence: 99%